The Ecstatic phenomenon in Polish traditional country music culture - Welcz, Henryk (Current Problems of Psychiatry, 2015)
Trance is a medical term contained in Chapter V of the International Statistical Classification of Diseases and Related Health Problems /ICD-10/, in the part concerning disassociational disorders /F44.3, together with possession/. The term denotes a disorder characterised by transitional loss of own identity and a decline of complete understanding of the surroundings. In this article, I want to deal only with some of the phenomena of trance that I have encountered, that is dependent on loss of will, and which is performed in Poland’s traditional musical culture as found in rural areas. The phenomena of trance and ecstasy, which are frequently co-identified, was named by the researchers of the subject as being a changed state of conscience or a changed mental state induced by physiological or psychological factors. This is characterised by the deviation in subjective understanding of the reality and a change towards approved forms of behaviour during the experience. Trance or ecstasy may occur during or after the singing of certain songs or the hearing or playing of particular traditional instrumental forms.